ANALISIS KEMAMPUAN MAHASISWA BIOLOGI YANG PPL TAHUN PELAJARAN 2002/2003 DALAM MERUMUSKAN TPK PADA MATERI SLTP SEMESTER I - Mariani Natalina; Diarty Agustin; Rosmega Titien (Biogenesis, 2004)
Study on the ability of the students in composing the TPK for the 1st, 2nd and 3rd year Junior High School students was conducted by the year of 2003  in the FKIP  UNR1, Pekanbaru.  Aims o f this study are toi understand the ability of the students in writing the TPK teaching materials and the ability of students in designing the TPK teaching methods. Data were obtained by analyzing the TPK paper works created by students. Result o f this study indicated that 63,53% TPK written for the  1st Junior High School student categorized  as  “fair”  and  the  other are “poor” , but the teaching method  of 98,34%  o f them  are well designed. Around 77% o f TPK for the 2nd year students are well written and the 94% o f them are well designed. The TPK for the 2nd year students, in contrast are poor written, but 98,99% are well designed Based on the results ,  it can be concluded  that the Biology  Study program  students are able to design the TPK, but they have low ability in writing this work. Key words : PPL, to design the TPK